Introduction - Arredondo Garrido, D.; Calatrava, J.; Sequeira, M. (Eating, building, dwelling: About food, architecture and cities, 2025)
The intricate relationship between food, city, and architecture, spanning from ancient civilizations to the present, serves as a focal point for interdisciplinary discourse. Engaging historians, sociologists, urban planners, and artists, it merges material realities with imaginative constructs. This book delineates three spatial levels – city, home, and intermediate spaces – illuminating their dynamic interplay within the construct of a continually evolving “food space.” Featuring 12 contributions from Mediterranean Europe, this publication explores historical legacies and contemporary challenges. Divided into urban-territorial and architectural scales, it offers nuanced insights into urban dynamics, domestic life and gastronomic tourism. Supported by a prestigious introductory study, this research advances a comprehensive understanding of food’s role in shaping urban environments. Chapters included in this publication have been developed within the framework of the research project: “Food and the City, from the domestic to the public space. Elements for a history, arguments for the contemporary project,” Grant PID2020–115039GB-I00, funded by MICIU/AEI/10.13039/501100011033.